WAYS TO INCREASE NATIONAL EXPORT COMPETITIVENESS IN THE DEVELOPMENT OF FOREIGN TRADE (ON THE EXAMPLE OF AGRICULTURAL PRODUCTS) - Shodmonova Nilufar Abdurashid qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Annotation. This thesis examines the strategies to enhance Uzbekistan’s national export competitiveness, particularly focusing on agricultural products, within the context of its foreign trade. The paper outlines the significance of agriculture as a key driver of Uzbekistan’s economy, given its vast natural resources and fertile lands. However, it highlights that the sector faces numerous challenges, including outdated infrastructure, limited product diversification, and inconsistent quality standards.